Eucalyptus growth and yield system: Linking individual-tree and stand-level growth models in clonal Eucalypt plantations in Brazil - Scolforo, Henrique Ferraco; McTague, John Paul; Burkhart, Harold; Roise, Joseph; Campoe, Otavio; Stape, Jose Luiz [UNESP] (Elsevier B.V., 2019)
Linking individual-tree and stand-level growth models is required for estimating future forest stand structure, while maintaining the desired accuracy for forest management decision making. There is a scarcity of studies addressing this issue for clonal Eucalypt stands in Brazil. Thus, this paper aims to develop a compatible individual-tree and stand-level growth and yield system for clonal Eucalypt stands in Brazil. The dataset used in this study is derived from remeasurement information of sixteen TECHS sites. At every site, eleven Eucalypt clones were planted in single block plots, while extra plots under a rainfall exclusion regime were also installed in fourteen sites. Prediction and projection diameter percentile equations were developed, as well as an individual-tree mortality equation and a generalized height-diameter equation. In addition, a detailed explanation of the structural architecture of the developed compatible growth and yield system is provided. Differences when forecasting forest afforestation and updating forest inventories were highlighted in order to provide the proper use of the developed growth and yield system. Finally, the individual-tree equations were validated through the use of the rainfall exclusion regime plots as was the growth and yield system when applied for prediction and projection purposes. The individual-tree level equations provided accurate estimates. The newly developed compatible growth and yield system also displayed unbiased and accurate estimates. The system achieved full compatibility between individual-tree and stand-level estimates and produced accurate stand table estimates. The growth and yield system presented is a powerful analytical tool that can serve to update inventory data in tropical Brazil and also to provide estimates for expected forest afforestation. The system has the capability of providing detailed outputs, which allows forest managers to consider merchandizing the clonal Eucalypt stands into multiple products.
Keywords: Multiple products; Compatibility; Climate variation; Consistency; Stand table